EFFECT OF PROFITABILITY AND WORKING CAPITAL ON COMPANY VALUE ON FOOD AND BEVERAGE COMPANIES ON THE INDONESIA STOCK EXCHANGE IN 2015-2019 - Kurniawan, Andri; Bisri , Bisri; Putra, Dian Berliansyah (AGUSPATI Research Institute, 2021)
The increasingly fierce development of the business world creates sharp competition between companies. Companies are required to have competitive advantages in technology, products, and human resources. In addition, the state of the Indonesian economy which is experiencing instability is a very significant phenomenon so that it becomes a threat to companies and cannot be separated from food and beverage companies. Every food and beverage sub-sector manufacturing company always wants to improve performance so that its goals can be achieved. The main objective of the company is to maximize the value of the company which can be measured from the share price of the company concerned. If the value of the company is higher, it means that the price to be received by the owner of the company will be even greater.This research was conducted to determine how much influence profitability and working capital have on firm value, either partially or simultaneously on food and beverage sub-sector issuers on the Indonesia Stock Exchange. The data collection method uses secondary data in the form of financial reports from the Indonesia Stock Exchange. The data obtained were then processed by multiple regression method with SPSS version 23.00 software. The results showed that the profitability partially has a significant effect on firm value. Working capital partially does not have a significant effect on firm value. Simultaneously, working capital and profitability have a significant effect on firm value.